2010
DOI: 10.1016/j.ijgo.2010.04.030
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of the efficacy of applying a simple acupressure protocol to the Taichong point in relieving dysmenorrhea

Abstract: Applying a simple pressure protocol to the Taichong acupoint was an effective and inexpensive way of decreasing the severity of dysmenorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…28 The Taichong acupressure group showed a significant decrease in dysmenorrhea severity (P < 0.01), and, by the fourth menstrual cycle, there was a significant difference in dysmenorrhea severity (P < 0.02) between the Taichong and placebo groups.…”
Section: Self-acupressure For Dysmenorrheamentioning
confidence: 87%
See 1 more Smart Citation
“…28 The Taichong acupressure group showed a significant decrease in dysmenorrhea severity (P < 0.01), and, by the fourth menstrual cycle, there was a significant difference in dysmenorrhea severity (P < 0.02) between the Taichong and placebo groups.…”
Section: Self-acupressure For Dysmenorrheamentioning
confidence: 87%
“…28,29 Lee and Frazier reported three RCTs showing pain scores that significantly decreased in the acupressure group in comparison with the control group. 3 Jiang et al conducted a meta-analysis of acupressure performed by participants or by practitioners and reported that the VAS, SF-MPQ, and SF-MDQ scores in the acupressure group were significantly better than in the control group.…”
Section: Dysmenorrheamentioning
confidence: 99%
“…All the 8 trials used a parallel design, including 800 patients [1522]. Six trials had two study groups [15, 16, 18, 19, 21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…Six trials had two study groups [15, 16, 18, 19, 21, 22]. One trials had three groups [20] and one trials had four arms [17].…”
Section: Resultsmentioning
confidence: 99%
“…SP6 and SP8 points acupressure helps to reduce pain severity of dysmenorrhoea up to 2 h after application 109 . Single point LI4 (Hegu), 110 LV3 (Taichong)111, 112 acupoint acupressure also helps to effectively reduce menstrual pain during primary dysmenorrhoea. Collateral meridian acupressure therapy (CMAT) is effective in relieving the associated symptoms of dysmenorrhoea and has to produce a long-lasting effect on dysmenorrhoea 113 .…”
Section: Acupressure Applicationsmentioning
confidence: 99%